2019
DOI: 10.1111/1751-7915.13482
|View full text |Cite
|
Sign up to set email alerts
|

Air‐side ammonia stripping coupled to anaerobic digestion indirectly impacts anaerobic microbiome

Abstract: Summary Air‐side stripping without a prior solid–liquid phase separation step is a feasible and promising process to control ammonia concentration in thermophilic digesters. During the process, part of the anaerobic biomass is exposed to high temperature, high pH and aerobic conditions. However, there are no studies assessing the effects of those harsh conditions on the microbial communities of thermophilic digesters. To fill this knowledge gap, the microbiomes of two thermophilic digesters (55°C), fed with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Regarding bacteria, the highest NH 4 + conditions corresponded to the highest diversity of overabundant taxa. Among them, Tepidimicrobium enrichment in experiment 1 was consistent with previous studies reporting its prevalence (also in association with Methanoculleus ) in continuous AD of nitrogen-rich substrates up to 6.5 g TAN liter −1 ( 67 , 77 ) and in batch assays at extreme ammonia concentration above 25 g liter −1 ( 50 ). However, depending on the operating conditions, Tepidimicrobium can also be inhibited at high TAN, as observed in high solid digester at 5 to 6 g N-NH 4 + liter −1 ( 52 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding bacteria, the highest NH 4 + conditions corresponded to the highest diversity of overabundant taxa. Among them, Tepidimicrobium enrichment in experiment 1 was consistent with previous studies reporting its prevalence (also in association with Methanoculleus ) in continuous AD of nitrogen-rich substrates up to 6.5 g TAN liter −1 ( 67 , 77 ) and in batch assays at extreme ammonia concentration above 25 g liter −1 ( 50 ). However, depending on the operating conditions, Tepidimicrobium can also be inhibited at high TAN, as observed in high solid digester at 5 to 6 g N-NH 4 + liter −1 ( 52 ).…”
Section: Discussionsupporting
confidence: 91%
“…The main SAO overexpressed at the highest ammonium level was affiliated with Syntrophaceticus . Known for its ammonia tolerance, Syntrophaceticus has been isolated from AD operating at 6.4 g N-NH 4 + liter −1 ( 79 ) and detected in ammonia-stripping AD ( 77 ). The amino acid degrader Gelria , known as syntrophic glutamate oxidizer ( 80 ), was also overabundant at high TAN in experiment 1, albeit in lower proportion.…”
Section: Discussionmentioning
confidence: 99%
“…This technological solution is considered, e.g., in digesters processing bio-waste containing nitrogen-rich co-substrates. Fernandez-Gonzalez et al [61] proposed to pair thermophilic reactors with an air-side stripping column operated 3 h, 3 to 5 times a week, and treating 21% of the reactor volume in each batch, at 65 • C and without a pH control. In these conditions, the bacteria community, assessed by 16S rRNA gene sequencing analysis, was mainly composed of Firmicutes, which on average represented 80.2% of biomass, followed by Bacteroidetes (8.6%).…”
Section: Simultaneous Ammonia Stripping Supporting Biological Ammoniumentioning
confidence: 99%
“…Serna-Maza et al [87] reported that introduction of side-stream stripping led to a decrease in TAN concentration (5 gN/kg to 3 gN/kg). In studies by Pedizzi et al [14] and Fernandez-Gonzalez et al [88], a decrease in TAN concentration from 2.5 to 1.1 g N/L in the digester and by a factor of 1/3, respectively, was observed upon re-circulation of stripped digestate. Inspite of the decreasing ammonia concentration in the stripping digesters, no significant change in methane yields was reported.…”
Section: Side-stream Strippingmentioning
confidence: 89%
“…Several studies have reported a decrease in ammonia concentration in the digester when side-stream stripping was implemented [14], [87], [88], [89]. Serna-Maza et al [87] reported that introduction of side-stream stripping led to a decrease in TAN concentration (5 gN/kg to 3 gN/kg).…”
Section: Side-stream Strippingmentioning
confidence: 99%